Impact On Punjab Of Socio-Religious Movements (1849-1900) - Daljit Kaur Gill (Elementary Education Online, 2023)
Due to the criticalsituation in Punjab, a number of socio-religious reform movements emerged in Punjab during 1849 to 1900 AD